Digital Design of Audio Signal Processing Using Time Delay - Perez, Mauricio; de Souza, Rodolfo Coelho; Faria, Regis Rossi Alves (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
This poster describes the design in PureData of some audio signals processes in real time like delay, echo, reverb, chorus, flanger e phaser. We analyze the technical characteristics of each process and the psychoacoustic effects produced by them in human perception and audio applications. A deeper comprehension of the consequences of sound processes based on delay lines helps the decision-making in professional audio applications such as the audio recording, mixing, besides music composition that employs sound effects in preprocessed or real-time.